Pertimbangan Hakim dalam Putusan Perkara Penadaan Mobil - Ida Bagus Mayun Andika Putra; Nyoman Gede Sugiartha; I Nyoman Subarnia (Fakultas Hukum, Universitas Warmadewa, 2021)
Cases in vehicle catching often occur given the increasing number of vehicle production increases. Someone commits the crime of motor vehicle theft because they want to own it, but the economy does not allow it to buy legally. One of the efforts to realize this is through restructuring because the price is much cheaper than the official price. The purpose of this research is to reveal the judges' considerations in the decision of car arresting cases and the criminal sanctions for car arresting offenders. The research method used is a normative research method with a conceptual approach and a case approach. The sources of legal materials used are primary and secondary sources of law. The technique of collecting legal materials is done by recording, quoting, reading, and summarizing the literature that refers to the judge's consideration in the decision of the car arresting case. After the legal materials are collected, they are analyzed systematically. The results of the study reveal that Article 480 of the Criminal Code is used as a criminal sanction for detention if the defendant is found guilty.